Family influence on disabled children exposure towards digital acceptance - Abd Rahman, Rozailin; Hashim, Junaidah; Wok, Saodah; Haque, A. K. M. Ahasanul (Zes Rokman Resources, 2018)
The past four decades have seen major developments in information technologies which have led to the production of many devices, which are being used for a wide range of applications for work, education, leisure and daily living. These developments have created some of the most promising possibilities yet available for solving or mitigating the problems of people with disabilities especially children. Most of them use the internet as a place for learning. Florian (2004), claims that the internet can be an exhilarating and helpful tool for educational purposes. They further suggested that there are multiple Web sites and software that can stimulate a better learning environment more than traditional learning does. Learning about basic computer operations, how to explore the internet and playing online games provide new knowledge as well as entertainments for them. The act of learning still takes place even with all the fun that they experienced (Moisey & Keere, 2007). This knowledge will help them to fit into places that they are not able to before such as internet cafés, online fairs and even game competition events. This study aims to find out how the family background may or may not influence on disabled children's exposure towards their digital acceptance. 395 disabled children all around Malaysia have been interviewed and their sociodemographic have been analysed.